Extracellular RNA as a Versatile DAMP and Alarm Signal That Influences Leukocyte Recruitment in Inflammation and Infection - Preissner, Klaus T.; Fischer, Silvia; Deindl, Elisabeth (Frontiers in Cell and Developmental Biology, 2020)
Upon vascular injury, tissue damage, ischaemia, or microbial infection, intracellular material such as nucleic acids and histones is liberated and comes into contact with the vessel wall and circulating blood cells. Such “Danger-associated molecular patterns” (DAMPs) may thus have an enduring influence on the inflammatory defense process that involves leukocyte recruitment and wound healing reactions. While different species of extracellular RNA (exRNA), including microRNAs and long non-coding RNAs, have been implicated to influence inflammatory processes at different levels, recent in vitro and in vivo work has demonstrated a major impact of ribosomal exRNA as a prominent DAMP on various steps of leukocyte recruitment within the innate immune response. This includes the induction of vascular hyper-permeability and vasogenic edema by exRNA via the activation of the “vascular endothelial growth factor” (VEGF) receptor-2 system, as well as the recruitment of leukocytes to the inflamed endothelium, the M1-type polarization of inflammatory macrophages, or the role of exRNA as a pro-thrombotic cofactor to promote thrombosis. Beyond sterile inflammation, exRNA also augments the docking of bacteria to host cells and the subsequent microbial invasion. Moreover, upon vessel occlusion and ischaemia, the shear stress-induced release of exRNA initiates arteriogenesis (i.e. formation of natural vessel bypasses) in a multistep process that resembles leukocyte recruitment. Although exRNA can be counteracted for by natural circulating RNase1, under the conditions mentioned, only the administration of exogenous, thermostable, non-toxic RNase1 provides an effective and safe therapeutic regimen for treating the damaging activities of exRNA. It remains to be investigated whether exRNA may also influence viral infections (including COVID-19), e.g. by supporting the interaction of host cells with viral particles and their subsequent invasion. In fact, as a consequence of the viral infection cycle, massive amounts of exRNA are liberated, which can provoke further tissue damage and enhance virus dissemination. Whether the application of RNase1 in this scenario may help to limit the extent of viral infections like COVID-19 and impact on leukocyte recruitment and emigration steps in immune defense in order to limit the extent of associated cardiovascular diseases remains to be studied.